Classical pathway activity C3c, C4 and C1-inhibitor protein reference intervals determination in EDTA plasma - Lopez, Benjamin (Array, 2019)
Reference intervals (RIs) for complement assays in EDTA plasma samples have not previously been published. The objectives of thepresent study were to validate and/or determine RIs for classical pathway (CP50) activity and C3c, C4 and C1 inhibitor protein (C1INH) assays and toassess the need for age-specific RIs in EDTA plasma.Materials and methods: We retrospectively evaluated a cohort of 387 patients attending our university hospital and known to be free of complement-modifying diseases. The need for age partitioning was assessed and RIs were calculated according to the CLSI protocol.Results: No need for age partitioning was evidenced for CP50 activity, C3c and C4 concentrations and RIs (90% CI) were calculated from the pooleddata: 35.4 (33.1-37.2) to 76.3 (73.7-83.6) U/mL for CP50 activity, 0.80 (0.75-0.87) to 1.64 (1.59-1.72) g/L for C3c, and 0.12 (0.10-0.14) to 0.38 (0.36-0.40) g/L for C4. Our results highlight a positive association between age and C1INH concentrations. We derived 3 age partitions (6 months to 30years, 30-50 and >50 years) and the related RIs: 0.20 (0.18-0.21) to 0.38 (0.36-0.40) g/L, 0.22 (0.20-0.24) to 0.39 (0.36-0.41) g/L and 0.25 (0.22-0.27)to 0.41 (0.40-0.43) g/L, respectively).Conclusions: The newly determined RIs for CP50 activity were higher than those provided by the manufacturer for EDTA plasma samples, whereasthose for C3c and C4 RIs were similar to the values provided for serum samples. The C1INH concentration and activity were found to be associatedwith age and age-specific RIs are mandatory for this analyte.